Design of Sustainable Renewable-Based Utility Plants in the Face of Uncertainty - Pérez-Uresti, Salvador I.; Martín, Mariano; Jiménez-Gutiérrez, Arturo (Frontiers in Sustainability, 2021)
This work presents the formulation of a two-stage stochastic MILP model to include uncertainty in the design of renewable-based utility plants. The model is based on a superstructure that integrates technologies to process biomass, waste, solar radiation and wind and considers uncertainty in availability of the renewable resources and on the utility demands. The uncertain parameter space is calculated based on a monthly probability density function for each uncertain parameter and discretized into different levels. It is shown that as uncertainty is considered in the model formulation, design flexibility improves with respect to the deterministic-based designs, although the flexibility is achieved at the expense of higher underused facilities and therefore unused investment cost.